Significance of Examined Lymph Node Number in Accurate Staging and Long-term Survival in Resected Stage I-II Pancreatic Cancer - More is Better? A Large International Population-based Cohort Study - Huang, Lei; Jansen, Lina; Balavarca, Yesilda; Van Der Geest, Lydia; Lemmens, Valery; Groot Koerkamp, Bas; Van Santvoort, Hjalmar C.; Grützmann, Robert; Besselink, Marc G.; Schrotz-King, Petra; Brenner, Hermann (Annals of Surgery, 2019)
Objective: This large international cohort study aimed to investigate the associations of examined lymph node (ELN) number with accurate staging and long-term survival in pancreatic adenocarcinoma (PaC) and to robustly determine the minimal and optimal ELN thresholds. Summary Background Data: ELN number is an important quality metric in cancer care. The recommended minimal ELN number in PaC to accurately stage cancer varies greatly across guidelines, and the optimal number especially to adequately stratify patient survival has not yet been established. Methods: Population-based data on patients with stage I to II PaC resected in 2003 to 2015 from the US Surveillance, Epidemiology, and End Results (SEER)-18 Program and Netherlands National Cancer Registry (NCR) were analyzed. Associations of ELN number with stage migration and survival were evaluated using multivariable-adjusted logistic and Cox regression models, respectively. The series of odds ratios (ORs) for negative-to-positive node stage migration and hazard ratios (HRs) for survival with more ELNs were fitted using a LOWESS smoother, and structural breakpoints were determined by Chow test. Results: Overall 16,241 patients were analyzed. With increasing ELN number, both cohorts exhibited significant proportional increases from nodenegative to node-positive disease [ORSEER-18=1.05, 95% confidence interval (CI) = 1.04-1.05; ORNCR = 1.10, 95% CI = 1.08-1.12] and serial improvements in survival (HRSEER-18 = 0.98, 95% CI = 0.98-0.99; HRNCR = 0.98, 95% CI = 0.97-0.99) per additional ELN after controlling for confounders. Associations for stage migration and survival remained significant in most stratifications by patient, tumor, and treatment factors. Cut-point analyses suggested a minimal threshold ELN number of 11 and an optimal number of 19, which were validated both internally in the derivative US cohort and externally in the Dutch cohort with the ability to well discriminate different probabilities of both survival and stage migration. Conclusions: In stage I to II PaC, more ELNs are associated with more precise nodal staging, which might largely explain the survival association. Our observational study does not suggest causality, and does not encourage more extended lymphadenectomy before further randomized evidence is obtained. Our results robustly conclude 11 ELNs as the minimal and suggest 19 ELNs as the optimal cut-points, for evaluating quality of lymph node examination and possibly for stratifying postoperative prognosis.
CRIS-Team Scopus Importer:2019-08-27
Keywords: accurate staging; examined lymph node count; large international population-based cohort study; long-term survival; pancreatic cancer; threshold